PENGALAMAN KELUARGA DALAM MERAWAT PENDERITA OSTEOARTHRITIS - Warsono Warsono; Faradisa Yuanita Fahmi; Ari Kurnia Rahma (Jurnal Surya Muda, 2023)
Osteoarthritis is one of the chronic degenerative diseases experienced by the elderly. Various changes that occur in the elderly affect the elderly in responding to the problems they cause. The family as a home health care provider will react to this response. This study aims to explore the experiences of families in caring for osteoarthritis. This study aims to determine the experience of families in caring for patients with osteoarthritis. Using qualitative research methods with a descriptive phenomenological approach, where researchers will describe, describe and describe clearly and in detail and get in-depth data and focus on the issues to be discussed. Participants were taken randomly from several families whose family members suffered from osteoarthritis. The number of participants in this study was nine participants. The results of this study identified two themes: family experience in caring for osteoarthritis sufferers and obstacles or obstacles in caring for osteoarthritis sufferers. It was concluded that the patients with osteoarthritis at home were mainly carried out by the families of the participants, both husbands, wives, and biological children. Experience in caring for people with osteoarthritis carried out by the family includes the family's efforts to overcome the symptoms experienced in osteoarthritis sufferers, experiencing changes in emotional responses, and experiences of support given by families to sufferers of osteoarthritis. Participants also shared their experiences about problems or obstacles experienced by families in caring for people with osteoarthritis and how to deal with these problems, such as experiencing a lack of knowledge in managing people with osteoarthritis and experiencing limitations in caring for people with osteoarthritis.